Geographic Accessibility of General Practitioners by Car and Public Transport - A Study Using the Minimum Travel Time Method in a Rural Area in the North-East of Germany - , Julia Hecht; , Bernhard Langer (Archives of Current Research International, 2024)
Basic medical care should be accessible to all people without restriction. However, the distribution of practices in rural areas is often limited to the centers, meaning that distances have to be covered. The Federal Joint Committee (G-BA), the highest decision-making body of the joint self-government of physicians, dentists, hospitals and health insurance funds in Germany, only states for cars that 95% of the population should be able to reach general practitioners (GPs) in less than 20 minutes on average. The aim of this study was to determine the geographic accessibility of GP practices by car and public transport. A cross-sectional study was conducted in a rural area in the north-east of Germany called Neustrelitz Central Zone and reported according to the STROBE statement. Geographic data of OpenStreetMap and the Federal Agency for Cartography and Geodesy and GP practices data of the Associations of Statutory Health Insurance Physicians Mecklenburg-Western Pomerania and Brandenburg were used. Based on the method of minimum travel time, the required travel times by car and public transport from the local centers to the three nearest physician locations were determined using various online tools. On average, inhabitants need 10.7 minutes to reach the three nearest GP practices by car, up to a maximum of 19 minutes. The average travel time by public transport for an appointment at 10 a.m. is four hours and twelve minutes. While it is possible for all municipalities (and their inhabitants) to reach the nearest GP practices in time for an appointment at 10 a.m. and to complete the return journey on the same day, this is no longer possible for 35% of municipalities (and their inhabitants) for an appointment at 3 p.m. and for 53% for an appointment at 5 p.m. In the Neustrelitz Central Zone, the accessibility of GP practices by car is ensured in accordance with the G-BA statements. On the other hand, the accessibility of GP practices by public transport can be a problem for people who do not have their own car. This could be remedied, for example, by expanding eHealth or mobile medical practices.